2017
DOI: 10.1044/2017_jslhr-l-17-0015
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Across Prematurity, Attention, and Language in School-Age Children

Abstract: Attention abilities are associated with children's language performance even in the absence of an attention-deficit/hyperactivity disorder diagnosis. Clinical implications, particularly as related to assessment, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Interestingly, no group differences were seen for the language variables obtained from the language samples. In a follow-up study, Mahurin-Smith, DeThorne, and Petrill (2017) found that attention skills, as measured by a parent report of attention skills, partially mediated the relationship between prematurity and outcomes on the standardized assessment, suggesting that poor attention skills may have accounted for poorer performance on the standardized assessments.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, no group differences were seen for the language variables obtained from the language samples. In a follow-up study, Mahurin-Smith, DeThorne, and Petrill (2017) found that attention skills, as measured by a parent report of attention skills, partially mediated the relationship between prematurity and outcomes on the standardized assessment, suggesting that poor attention skills may have accounted for poorer performance on the standardized assessments.…”
Section: Resultsmentioning
confidence: 98%
“…Third, cardiac measures change during phases of attention [Richards, ]. More vagal control during calm viewing could reflect stronger control of endogenous attention, and thus be important to domains that require focused attention like language learning [Mahurin‐Smith, DeThorne, & Petrill, ]. Indeed, higher fetal PNS activity predicts better language skills at 2.5 years [DiPietro, Bornstein, Hahn, Costigan, & Achy‐Brou, ].…”
Section: Introductionmentioning
confidence: 99%
“…Language and attention represent two crucial cognitive processes in developing children. The relationship between these two cognitive processes has led to discussion in recent literature devoted both to typical development and to a range of developmental disorders in children (e.g., Calvo & Bialystok, 2014; Jongman, Roelofs, Scheper, & Meyer, 2017; Mahurin-Smith, deThorne, & Petrill, 2017). Language and attention may interact and shape each other in multiple ways.…”
mentioning
confidence: 99%